Nekateri vidiki doživljanja žensk ob operativnem posegu na rodilih - Trojar, Špela (Obzornik zdravstvene nege, 2013)
Introduction: Surgery is often the most effective first-line therapy of several gynaecologic conditions. All women undergoing gynaecologic surgery can benefit from presurgical and postsurgical support provided by nurses. Personalized nursing, tailored to the individual woman's needs enhances the patient's coping strategies and alleviates different adverse psychological sequelae following gynaecologic surgery. The objective of the study was to determine the differences in emotional experiences of gynaecological surgery and the significance of psychological support on the part of the patient's partner or her family as well as nurses. Methods: The study was designed as a case study, a form of qualitative descriptive research. A semi-structured non-standardised interview was used as the sole research instrument. It consisted of two sets of guided open-ended questions. The interviews were conducted with two patients with gynaecological condition in whom myomectomy was performed via a laparotomy and vaginal hysterectomy, respectively. The first part of the study was carried out in the Gynaecology and Obstetrics Hospital Kranj and the second part in the patients' home environment four to five weeks after discharge from the hospital. Results: Results of the study show that psychological aspects of gynaecologic surgery may differ depending upon the type of surgery performed and the risk factors in the preoperative period. The respondents' post-surgery responses revealed different perceptions of the self-concept and femininity following gynaecological surgery, and the dimension of nurses' perioperative support. Both patients, however, were relieved of frustrating pain and other physical symptoms after the surgery. Discussion and conclusion: The conclusions drawn from the present study are that further research is needed on psychological aspects and implications of gynaecologic surgeries and their translation into clinical settings. Gynaecologic surgery patients must cope with a variety of psychological adjustment difficulties, related to the changes in self-image, self-esteem, loss of femininity or identity and sexual dysfunction. The likelihood of post-surgical psychological problems can be decreased by proper, streamlined and patient-oriented perioperative nursing care.
Keywords: fenomenološka študija; hysterectomy; miomi; myomas; nursing; samopodoba; self-esteem; tumors; uterine prolapse; zdravstvena nega; zdrs maternice